AB0102 SPECIALIZED PRO-RESOLVING MEDIATOR RECEPTORS AS INFLAMMATORY RESOLUTION BIOMARKERS IN RHEUMATOID ARTHRITIS. (13th June 2020) - Perniola, S.; Alivernini, S.; Tolusso, B.; Gigante, M. R.; Gessi, M.; Di Mario, C.; Petricca, L.; Capacci, A.; Fedele, A. L.; Ferraccioli, G.; Gremese, E.
Abstract : Background: The regulation of inflammation is a dynamic process involving several molecules as lipid mediators. The Specialized Pro-resolving Mediators (SPMs), such as Resolvin (RvD and RvE), Protectins, Maresins and Lipoxin A4 (LXA4), are bioactive metabolites of omega-3 and omega-6 fatty acids which drive inflammatory resolution phase and promote tissue repair. ERV, ALX/FPR2 and BLT1 are SPM receptors. Although in Rheumatoid Arthritis (RA) lipid mediators role within pathophysiology is under definition, studies on SPMs receptors role are still lacking in this disease. Objectives: Purpose of this study is to define ERV, ALX/FPR2 and BLT1 expression in blood derived leukocytes and synovial cells and to correlate it to disease activity to define SPM receptors ad inflammatory resolution biomarkers in RA patients. Methods: A cohort of 52 RA patients was enrolled in the study of which 40 with active disease (DAS28= 5, 35 (5, 18-6, 40)) and 12 in sustained remission status (DAS28= 2, 1 (1, 83-2, 42)). Each enrolled patient underwent peripheral blood (PB) drawing and 46 of them underwent US-guided synovial tissue (ST) biopsy. FACS gating strategy was used for PB and ST processing to evaluate percentage of positive cells and the mean fluorescence intensity (MFI) of ERV +, ALX/FPR2 + and BLT1 + in CD45 + CD3 +, CD45 + CD19 + for PB and ST, CD45 + CD14 + and neutrophils for PB only and CD45 - CD90 +, CD45 + CD64 + CD11b + macrophages (distinct in CD206 + and CD206 - subpopulations) for ST only. Each included ST was stained with haematoxylin/eosin and categorized by a pathologist, blinded to clinical characteristics, using the Krenn Score (KS) to assess ST inflammation degree. As control group, 11 undifferentiated peripheral inflammatory arthritis (UPIA) patients were enrolled in the study. Results: Considering the whole RA cohort, DAS28 inversely correlated with BLT1 + positive cells on ST-derived CD45 + (r= -0.48; p= 0.048), CD3 + (r= -0.56; p= 0.019) and CD19 + (r= -0.49; p= 0.042) cells, in contrast with CD90 + (r= 0.50; p= 0.041) cells. Similarly, both DAS28 and KS inversely correlated with ALX/FPR2 + positive cells in ST-derived CD45 + (r= -0.42, p= 0.050 and r= -0, 41, p= 0, 046 respectively) cells. Evaluating the MFI levels of the SPM receptors along all RA stages (naïve-to-treatment, resistant-to-treatment, sustained remission) compared with UPIA control group, interestingly ST-derived CD45 + cells of remission RA were depleted of ERV1 compared to naïve-to-treatment RA (p=0.04), despite comparable ST inflammation. Furthermore, highest ERV1 expression was found in ST-derived CD45 + CD3 + and CD45 + CD19 + cells in naïve-to-treatment RA compared with UPIA patients (p= 0, 045 and p= 0, 012 respectively). Moreover, the lowest BLT1 level was found in remission RA CD3 + cells compared with UPIA and naïve-to-treatment RA patients (p= 0, 008 and p= 0, 023 respectively). Conclusion: SPM receptors expression seem to be tightly related to disease activity in the synovial tissue, suggesting an important involvement in the inflammatory process in RA patient. References: [1]Serhan CN. Nature, 2014. [2]Alivernini S, et al. Arthritis Res Ther 2016 [3]Krenn V et al. Histopathology, 2006. Disclosure of Interests: Simone Perniola: None declared, Stefano Alivernini: None declared, Barbara Tolusso: None declared, Maria Rita Gigante: None declared, Marco Gessi: None declared, Clara Di Mario: None declared, Luca Petricca: None declared, Annunziata Capacci: None declared, Anna Laura Fedele: None declared, Gianfranco Ferraccioli: None declared, Elisa Gremese Speakers bureau: Abbvie, BMS, Celgene, Jannsen, Lilly, MSD, Novartis, Pfizer, Sandoz, UCB